Use of nasopharyngeal culture to determine appropriateness of antibiotic therapy in acute bacterial rhinosinusitis. Issue 4 (25th October 2012) - Lee, Stella; Woodbury, Kristin; Ferguson, Berrylin J.
<x xml:space="preserve">Abstract</x> Background Rhinosinusitis is one of the top 5 diagnoses for which an antibiotic is prescribed, often without a clear bacterial etiology. This study evaluated whether nasopharyngeal culture and gram stain could serve as a surrogate for endoscopically obtained middle meatal cultures in directing appropriate therapy for acute bacterial rhinosinusitis (ABRS). This study also investigated the utility of a rapid sinus test screen in differentiating bacterial from nonbacterial rhinosinusitis. Methods Thirty‐one adult patients met inclusion criteria for ABRS. Samples were obtained from both the middle meatus and nasopharynx for Gram stain and culture. Nasal mucous samples were tested with a rapid sinus test strip measuring pH, levels of protein, nitrites, and leukocyte esterase. Results Sixty‐one percent (61%) of nasopharyngeal and 48% of middle meatal samples grew pathogenic bacteria. The concordance rate was 84% between the 2 sites (p = 0.0006). The following pathogenic organisms were detected: Moraxella catarrhalis, Streptococcus pneumoniae, Haemophilus influenzae, Pseudomonas aeruginosa, and Staphylococcus aureus. For nasopharyngeal samples, reliance on Gram stain alone exhibited a sensitivity of 31% and specificity of 100% and, similarly, for middle meatus samples, 47% and 93%, respectively. The rapid sinus test revealed a sensitivity of 83% and specificity of 7%. Conclusion Nasopharyngeal and middle meatal cultures exhibited high concordance for pathogenic bacteria. Gram stain exhibited moderate sensitivity and excellent specificity. Nasopharyngeal cultures could provide a viable method, especially in a primary care setting, for determining the appropriateness of antibiotic therapy. The rapid sinus test's lack of specificity precluded its utility in the differentiation between bacterial and nonbacterial rhinosinusitis.